A five-year development plan for the Asean Regional Centre for Biodiversity Conservation (ARCBC) Library - Annex, Quezon City a proposal - Garcia, Glenn E. (2001)
This study focused on the formulation of a five-year development plan for the ASEAN Regional Centre for Biodiversity Conservation (ARCBC) Library Annex, Quezon City. It presented the present condition of the library in terms of personnel, collection, facilities, services, and funding. A survey was conducted to evaluate the library and elicit the information needs of the ARCBC Co-directors and annex staffs.